“Insular hobbits”? Englishness, Euroscepticism and the Brexit vote in Jonathan Coe’s Middle England (2018) - Guillaume Clément (Revue LISA)
In Middle England (2018), novelist Jonathan Coe revisits some events of Britain’s recent past in order to highlight, in fictional form, some potential reasons for the Brexit vote and to illustrate the widening political divides among the population. Among other factors, Coe’s satire draws our attention to contemporary representations of Britishness in media and popular culture, for instance in the London 2012 Olympic games’ opening ceremony, with its quite stereotypical, anglocentric portrayal of national identity. Such depictions appear closer to the outdated mythical tropes of “Deep England” than to the complexities of contemporary Britishness and might have helped fuel Eurosceptic rhetoric and influenced conservative English voters’ beliefs in the run-up to the 2016 EU membership referendum.